ANALISIS WAKTU TUNGGU PELAYANAN RESEP PADA PASIEN RAWAT JALAN DI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG - Subur Widodo; Masyuri Yusuf; M. Desirwan Dinata (JFL : Jurnal Farmasi Lampung, 2020)
Abstract Pharmaceutical services are health services in hospitals that are expected to meet minimum service standards (SPM) in an effort to improve the quality of services to patients. One of the pharmaceutical service categories in the minimum service standard (SPM) in hospitals is the waiting time for prescription services in the form of nonconcoction drugs is the grace period from the time the patient submits a prescription to receiving non-concoction drugs with a minimum standard set by the Ministry of Health that is ≤ 30 minutes, whereas the waiting time for prescription concoction services is the grace period from the time the patient submits the prescription until receiving the concoction drug that is ≤ 60 minutes. This research was conducted to analyze the waiting time for outpatient prescription services in Dr. H. Abdul Moeloek based on hospital minimum service standards (SPM) as an overview of prescription services, evaluation materials and pilots in an effort to improve the quality of pharmaceutical services. This research will be conducted at the pharmacy outpatients Dr. H. Abdul Moeloek in August - September 2019 with a sample of 172 recipes, consisting of 98 non-concoction recipes and 74 recipe concoctions. Based on the research that has been done, the results of waiting time for non-concoction prescription services in the Outpatient Installation of Dr. H. Abdul Moeloek is in accordance with the SPM at the Hospital with an average waiting time of 11 minutes. Waiting time for prescription concoction services in Dr. Outpatient Hospital Installation H. Abdul Moeloek is in accordance with the SPM at the Hospital with an average waiting time of 19.4 minutes. Keywords: Pharmaceutical services, waiting time, pharmaceutical service standards.